A Statistical Analysis of Evaporative Pattern Casting Process Parameters for the Production of Aluminum Alloy Components - Omidiji, B. Victor (Journal of Casting & Materials Engineering, 2020)
Four process parameters were investigated with the aim of determining their influence on the mechanical properties of some test castings, bars, cylinders and plates. The influence was quantified in terms of percentage contribution. Analysis of variance (ANOVA), regression, main effects and interaction effects plots were employed to carry out the statistical analysis. As regards the tensile strength of the test castings, the geometry of components (GOC) dominated, contributing 90.83% and the pouring temperature (PT) contributed 91.90% influence on the hardness property. These dominating potentials of these two parameters limited the interaction of the parameters studied in the research.